Profiling the Gut Microbiome of Hylobatidae and Cercopithecinae : Insights Into the Health of Primates in Captivity - Roberta Chaya Tawie, Tingga; Mohd Ridwan, Abd Rahman; Azroie, Denel; Badrul Munir, Md Zain (John Wiley & Sons Ltd., 2025)
A healthy gut microbiome is essential for digestion in primates, for developing the gut immune system, and for defense against pathogen invasion. Next-generation sequencing allows for determining the microbiome composition and enables the continuous monitoring of primate health.To comprehensively analyze the gut microbiome diversity of three endangered primate species at Matang Wildlife Centre—Hylobates abbotti, Macaca fascicularis, and Macaca nemestrina, using high-throughput sequencing of the 16S rRNA gene. A total of 18 phyla, 84 families, 188 genera, and 46 species were successfully classified. H. abbotti exhibited the highest microbial diversity with a distinct microbiome profile from the Macaca species. The presence of Treponema (nonpallidum), Bifidobacterium, and Faecalibacterium prausnitzii is critical for gut health, promoting digestion and maintaining the microbial balance. This study highlights the importance of monitoring microbial diversity in captive primates to better understand their health and facilitate the early detection of potential pathogens. This also offers insights into microbiome-based strategies for improving overall animal welfare.